Is Cervical Stabilization for All Cases of Chiari-I Malformation an Overkill? Evidence Speaks Louder Than Words! - Harsh Deora; Sanjay Behari; Jayesh Sardhara; Suyash Singh; Arun K. Srivastava (Neurospine, 2019)
Chiari I malformation is characterized by the downward displacement of cerebellar tonsils through the foramen magnum. While discussing the treatment options for Chiari I malformation, the points of focus include: (1) Has the well-established procedure of posterior fossa decompression become outdated and has been replaced by posterior C1–2 stabilization in every case? (2) In case posterior stabilization is required, should a C1–2 stabilization, rather than an occipitocervical fusion, be the only procedure recommended? The review of literature revealed that when there is bony instability like atlantoaxial dislocation (AAD), occipito-atlanto-axial facet joint asymmetry or basilar invagination (BI) associated with Chiari I malformation, one should address the anterior bony compression as well as perform stabilization. This takes care of the compromised canal at the foramen magnum and re-establishes the cerebrospinal fluid flow along the craniospinal axis; and also provides treatment for CVJ instability. In the cases with a pure Chiari I malformation without AAD or BI and with completely symmetrical C1–2 joints, however, posterior fossa decompression with or without duroplasty is sufficient to bring about neurological improvement. The latter subset of cases with pure Chiari I malformation have, thus, shown significant (>70%) rates of neurological improvement with posterior fossa decompression alone. A C1–2 posterior stabilization is a more stable construct due to the strong bony purchase provided by the C1–2 lateral masses and the short lever arm of the construct. However, in the cases with significant bleeding from paravertebral venous plexus; a very high BI, condylar hypoplasia and occipitalized atlas; gross C1–2 rotation or vertical C1–2 joints with unilateral C1 or C2 facet hypoplasia, as well as the presence of subaxial scoliosis; maldevelopment of the lateral masses and facet joints (as in very young patients); or, the artery lying just posterior to the C1–2 facet joint capsule (being endangered by the C1–2 stabilization procedure), it may be safer to perform an occipitocervical rather than a C1–2 fusion.